Development of spiritual intelligence model for adolescents in Malaysia / Shamsiah Banu Mohamad Hanefar - Shamsiah Banu, Mohamad Hanefar (2015)
Education in Malaysia is undergoing a transformation period from knowledge based education to value based (holistic) education which is being clearly objectified in the National Philosophy of Education (NPE), but there is a gap between the current practices in our education industry with the NPE. Many social problems among adolescents are being reported that are alarming and could be the hindrance factor for Malaysia in achieving its Vision 2020. This study is focused on developing a spiritual intelligence model for adolescents (SIMA) in Malaysia with the objectives to identify the need for designing the model, to develop the SIMA from the perspective of Imam al-Ghazali and Hasan Langgulung and finally to evaluate the SIMA. Design and Developmental Research (DDR) was used in this study which involved three phases. In the first phase, SI needs analysis was conducted amongst students, adolescents, parents, and educators. The majority of the respondents valued spiritual intelligence as an important element and highly needed by adolescents. In the second phase; design and development, content analysis was done using texts from the renowned spiritual scholar, Imam al-Ghazali and educationist, Hasan Langgulung. Seven major components of SI were identified to build the SIMA: (1) meaning/ purpose of life, (2) consciousness. (3) transcendence, (4) spiritual resources, (5) self-determination, (6) reflection - soul purification, (7) spiritual coping with obstacles. In the final phase, the SIMA was evaluated using fuzzy Delphi method. A set of questionnaire containing the major seven components of SI with 34 sub-items was evaluated and validated by 10 experts. All the components reached a consensus of 75% and above and were accepted as the important components to build the SIMA. The built model is necessary in providing guidelines towards the achievement of success and to overcome social problems among adolescents in Malaysia.